Freezing enhances CO 2 mineralization in Ca 2+ -containing solutions - Minghao Sun; Dong Gao; Bowen Li; Joseph S. Francisco; Guoying Bai; Xinxing Zhang (Proceedings of the National Academy of Sciences, 2025)
Natural carbon sinks and the factors influencing them are critical to the global carbon budget. Here, we identify the freezing process as an important factor. It greatly contributes to natural carbon sinks by enhancing atmospheric CO 2 sequestration/mineralization in mineral ion-rich aqueous systems, which is demonstrated by freezing the solutions of Ca(OH) 2 , binary NaCl–CaCl 2 solutions, and artificial seawater. The acceleration is caused by the impacts of freezing on nucleation and growth processes of CaCO 3 crystals. Freezing accelerates nucleation by concentrating reactants within ice crystal boundaries, increasing supersaturation, and thus lowering the nucleation energy barrier. At the post–thaw stage where nuclei already form and reactant concentration is decreased, the crystals undergo the barrier-free growth process. Our findings reveal the freezing-enhanced CO 2 sequestration that is omitted in the current global carbon budget models and signal an urgent need to integrate cryogenic mineralization into climate predictions.